PERAN MASYARAKAT MADANI DALAM MENGURANGI STIGMA DAN DISKRIMINASI TERHADAP PENDERITA HIV & AIDS - Ade Latifa; Sri Sunarti Purwaningsih (Research Centre for Population, Indonesian Institute of Sciences, 2011)
Policies and programs to prevent and control the HIV & AIDS cases have been conducted in Indonesia since many years ago, however, stigma and discrimination towards the people living with HIV & AIDS (PLWHA) are still existing and difficult to be eliminated People living with HIV & AIDS, often receive stigma. The HIV & AIDS was regarded as a disease curse from the God due to the negative behavior. Based on the study conducted in lndramayu and Bandung in 2009 this paper highlighted some important issues related to the role of civil society in reducing HIV &AIDS stigma and discrimination. This paper shows that the provision of law is not sufficient to handle the problem due to the limitation of law/ regulation scope in stating the issuess comprehensively. Issue like stigma and discrimination has not yet receive serious attention. Therefore, the role of civil society are very important for their capability to initiate dialog with the society to eliminate the stigma that tend to discriminate the PLWHA.Keywords: HIV & AIDS, stigma, discrimination, civil society